Gender and age features in adults with congenital heart disease - I.G. Lebid (Кардіохірургія та інтервенційна кардіологія)
The aim – to estimate effect of age and sex differences on risk of cardiac and surgical treatment and on follow-up after surgery in adulthood in patients with сongenital heart disease (СHD). Materials and methods. Between April 1, 2011 and December 31, 2015, there were included 2044 consecutive patients with CHD. To study the distribution of CHD, we divided patients into 11 groups according to the CHD nomenclature (every group included at least more than 40 pts). All patients were also divided into those that earlier had surgical/percutaneous interventions and never operated adults with CHD. There were two groups: group 1 – adults after interventions in adulthood (first-time and reoperation), group 2 – adults without any procedures after 18 years. Results. Among 2044 adults with CHD, 1059 (52 %) were male and 985 (48 %) women, and the median age was 26.23 ± 0.24 (range limits, 18–88 years) at the time of inclusion. In the overall population patients that already had a surgical/percutaneous intervention dominated (n = 1295; 63.4 %), compared to adults without any intervention (n = 749; 36.6 %). Group 2 (n = 1625; 79.5 %) included much more patients than group 1 (n = 419; 20.5 %). Overall mortality was 0.34 %. In total, seven adults died, including five males (0.47 %) and two women (0.20 %) without significant differences. The vast majority of including patients (n = 1837) were younger than 40 years. The annual number of examined patients with CHD progressively increased (from 221 in 2011 to 418 patients in 2015). Female patients with CHD had significantly more often arrhythmia history (236 women compared to 201 male patients, p < 0.05), significantly higher degree of heart failure class > 1 NYHA (453 women and 285 men, p < 0.05), and significantly more often required medications (660 women and 466 men, p < 0.05). Men smoked more often than women. Conclusions. The age peculiarities of patients with CHD were prevalence of patients younger than 40 years old, with no significant gender differences. The annual increasing in the total number of adult patients with CHD aged over 18 and over 40 years was registered.